Siargao pacific beach resort : Gen. Luna, Surigao del Norte - Bigno, Nilo S. (Manila : National University, 1997)
This study tenders the needed materials in a firm and precise manner, in as many words as are required and no more.
Approval sheet -- Dedication -- Acknowledgement -- Preface -- Chapter 1. Introduction -- Chapter 2. Methodology -- Chapter 3. Terms of references -- Chapter 4. Design framework -- Chapter 5. Summary -- Chapter 6. Appendices.
Includes bibliographical references.
Keywords: BEACH RESORT -- PLANNING